Discontinuation of primary and secondary prophylaxis for opportunistic infections in HIV-Infected Patients Who Had CD4+ Cell Count <200 cells/mm3 but Undetectable Plasma HIV-1 RNA: An Open-Label Randomized Controlled Trial - Chaiwarith R. (2014)
The CDC recommends discontinuing opportunistic infections (OIs) prophylaxis in HIV-infected patients who have CD4+ cell count >200 cells/mm3 after receiving combination antiretroviral therapy (cART). A prospective randomized controlled trial was conducted at Chiang Mai University Hospital from June 1, 2009 to January 31, 2012 in 74 adult HIV-infected patients who had received cART and had CD4+ cell count <200 cells/mm3 but plasma HIV-1 RNA<50 copies/ml. Forty-three patients (58.1%) were male and the mean age was 41.8±8.1 years; 68 (91.9%) and 59 (79.7%) patients were receiving co-trimoxazole and antifungal prophylaxis, respectively. The median CD4+ cell counts at enrollment were 142 (IQR 108, 161) and 158 (IQR 141, 176) cells/mm3 among patients who discontinued and continued OIs prophylaxis, respectively (p value=0.041). One of 37 patients (2.7%) in the discontinuation group developed Pneumocystis jiroveci pneumonia, giving the incidence rate of 1.57/1000 person-months. None of the 37 patients in the continuation group developed OIs. The difference in the prevention rates of OIs between groups was -2.7% (95% CI -7.9, 2.5). In conclusion, in the setting where plasma HIV-RNA measurement is available, e.g., Asia-Pacific region, discontinuation of prophylaxis is considerably safe in HIV-infected patients receiving cART with undetectable plasma HIV-RNA but incomplete immune recovery. © Copyright 2013, Mary Ann Liebert, Inc. 2013.